Hubungan antara kualitas pelayanan pegawai dengan kepuasan dan minat kunjungan ulang pasien rawat jalan di puskesmas nguter sukoharjo - Hartanto, Deky, Tri Puji Kurniawan, SKM, M. Kes, Kusuma Estu Werdani, SKM., M.Kes (2014)
Quality is the standard that must be achieved by someone who works at the health center. Quality of service employees have an impact on patient satisfaction, so that patients have an interest in re-visit to the clinic. The purpose of this study was to determine the corelation of service quality and satisfaction of employees to re-visit interest outpatient health center Nguter Sukoharjo. This research is analytic observational study with cross sectional design. The experiment was conducted at the health center Nguter, Sukoharjo. The population in this study is a new patient who went to the health center Sukoharjo Nguter numbered 625, the number of samples in this study 94 patients. Sampling with incidental sampling. Analysis of data using simple regression. The conclusion of this study are: (1) The test results simultaneously which shows the corelation of service quality employees with patient satisfaction results indicated r = 0.609, p = 0.000 (p <0.05) which means that the quality of service of have an corelation on patient satisfaction. That is, the higher the quality of services provided corelation, the higher patient satisfaction. Great corelation R² = 0.371 results indicated or 37,1%. (2) The test results are shown simultaneously test results r equal to 0.652, p = 0.000 (p <0.05) which means that the quality of service of associated with the interest of repeated requests simultaneously. That is, the higher the quality of services provided corelation, the higher the interest of patients do visit again. Great corelation R² = 0.426 results indicated or 41.6%.